Weak solutions to the two-dimensional steady compressible Navier–Stokes equations. (April 2017) - Zhong, Xin
Abstract: We study motions of the steady compressible viscous isothermal fluids in a bounded two dimensional domain governed by the Navier–Stokes equations. We obtain that there exists at least one weak solution to such a problem satisfying some integrability. The proof of this result is based on delicate estimates for the momentum equations and a bootstrapping argument.